2021
DOI: 10.1002/fsn3.2409
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the metabolic network of organic acids in solid‐state fermentation of Chinese cereal vinegar

Abstract: Vinegar, as a traditional fermented food, is an indispensable condiment in the world. Shanxi aged vinegar (SAV) is known as one of the most famous vinegar in China, which is fermented with solid-state fermentation (SSF) technology with sorghum as the main raw material (Tang et al., 2019). Organic acids are the key flavor compounds, contributing unique characteristics of SAV (Chen et al., 2016). The composition of organic acids is one of the main differences of diverse kinds of vinegar. It was reported that a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…Microbial enzymes in the later stage convert pyruvic acid into intermediate metabolites, which in turn produce various flavor compounds in vinegar, especially acetic-, and lactic acid. However, lactic acid is difficult to volatilize, and the taste threshold is not as good as that of acetic acid, which makes acetic acid the main flavor organic acid in vinegar ( Wu et al, 2021a ). Acetic acid has a strong, pungent odor, whereas lactic- and other organic acids neutralize the pungent odor of acetic acid and soften its flavor ( Krusong et al, 2020 ; Xu et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial enzymes in the later stage convert pyruvic acid into intermediate metabolites, which in turn produce various flavor compounds in vinegar, especially acetic-, and lactic acid. However, lactic acid is difficult to volatilize, and the taste threshold is not as good as that of acetic acid, which makes acetic acid the main flavor organic acid in vinegar ( Wu et al, 2021a ). Acetic acid has a strong, pungent odor, whereas lactic- and other organic acids neutralize the pungent odor of acetic acid and soften its flavor ( Krusong et al, 2020 ; Xu et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Xu et al (2022) explored the characteristic flavor compounds of fresh and aged coconut water vinegar and found 17 key metabolic pathways and 3 key metabolic substrates; namely, aspartic, glutamic and pyruvic acid. Wu et al (2021a) reconstructed the metabolic network of key organic acids with an OAV higher than 1 through the theory of flavor-orientation, and revealed the predominant genus ( Acetobacter , Lactobacillus ) for organic acid metabolism. This provided a preliminary understanding of the formation mechanism of vinegar flavor compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The raw materials for Sichuan Baoning vinegar production include wheat bran, water, vinegar Pei collected from a previous batch (also known as vinegar Pei residue, the remaining fermentation mixture after vinegar leaching), Daqu, and wheat flour. Vinegar brewing is a process that involves a variety of microorganisms, mainly mold, yeast, and acetic acid bacteria ( Wu et al, 2021 ). Due to the open fermentation, seasonal dynamics on climate may introduce differences in biodiversity and richness of microorganisms in the raw materials and environment.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the open fermentation technology, multiple microorganisms including molds, yeasts, and bacteria co-exist in the SSF process ( Wu et al, 2021a ). Studies have shown that LAB and acetic acid bacteria (AAB) are the two dominant bacteria in the SSF process ( Nie et al, 2013 ; Wu et al, 2021b ; Huang et al, 2022a ). Lactic acid and acetic acid are the most important organic acids in vinegar, accounting for more than 90% of the total acid, which are produced by LAB and AAB ( Wu et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that LAB and acetic acid bacteria (AAB) are the two dominant bacteria in the SSF process ( Nie et al, 2013 ; Wu et al, 2021b ; Huang et al, 2022a ). Lactic acid and acetic acid are the most important organic acids in vinegar, accounting for more than 90% of the total acid, which are produced by LAB and AAB ( Wu et al, 2021b ). The most common LAB and AAB in cereal vinegar fermentation are Lactobacillus helveticus and Acetobacter pasteurianus ( Huang et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%